Do racing drivers practice racing? The effect of intentional following on formula car drivers’ steering behaviour - Rosalie, Simon; Malone, James (2019)
Overtaking in formula car racing often requires close following to gain the benefits of slipstreaming. Research in road driving suggests that following another car closely causes a reallocation of visual attention to a narrower visual search strategy. In formula car racing, drivers’ visual search strategy is based on head movement rather than eye movement and is tightly coupled to their steering behavior. Therefore, a change in visual search strategy may affect a formula car driver’s steering behavior. We used electromyography to investigate whether skilled amateur formula car drivers (n= 4) transferred stable patterns of neck, shoulder girdle, and trunk muscle activation from a task that required them to drive on a clear track to a task that required them to follow another car closely. Rates of fatigue decreased in the muscles of the neck when drivers followed another car suggesting that head movement decreased, consistent with a narrowing of visual search. Concomitant changes occurred in the activation patterns of drivers’ shoulder girdle and trunk muscles. The findings imply that the drivers have not practiced following another car sufficiently to maintain stable bimanual coordination patterns for steering when attentional demand is increased in tasks typical of racing. Our results should be taken cautiously because of the small number of drivers tested. However, further studies are warranted to investigate how attentional demands affect formula car drivers’ coordination patterns for steering.